Viral nucleoprotein antibodies activate TRIM21 and induce T cell immunity. (1st December 2020) - Caddy, Sarah L; Vaysburd, Marina; Papa, Guido; Wing, Mark; O'Connell, Kevin; Stoycheva, Diana; Foss, Stian; Terje Andersen, Jan; Oxenius, Annette; James, Leo C
Abstract: Nucleoprotein (N) is an immunodominant antigen in many enveloped virus infections. While the diagnostic value of anti‐N antibodies is clear, their role in immunity is not. This is because while they are non‐neutralising, they somehow clear infection by coronavirus, influenza and LCMV in vivo . Here, we show that anti‐N immune protection is mediated by the cytosolic Fc receptor and E3 ubiquitin ligase TRIM21. Exploiting LCMV as a model system, we demonstrate that TRIM21 uses anti‐N antibodies to target N for cytosolic degradation and generate cytotoxic T cells (CTLs) against N peptide. These CTLs rapidly eliminate N‐peptide‐displaying cells and drive efficient viral clearance. These results reveal a new mechanism of immune synergy between antibodies and T cells and highlights N as an important vaccine target. Synopsis: Cytosolic antibody receptor and ubiquitin ligase TRIM21 promotes antigen presentation and T cell activation by targeting immune complexes for efficient proteasomal degradation. Non‐neutralizing, anti‐nucleoprotein antibodies provide immune protection by stimulating cytotoxic T cell (CTL) activity. Anti‐nucleoprotein antibodies are dependent upon TRIM21 for their activity. TRIM21 and anti‐nucleoprotein antibodies help resolve LCMV infection in mice. TRIM21 promotes in vivo T cell killing. Abstract : Cytosolic antibody receptor and ubiquitin ligase TRIM21 promotes antigen presentation and T cell activation by targeting immune complexes for efficient proteasomal degradation.